The Influence of Self-Concept on Citizenship Learning Outcomes - Rida Hatiarsih (STAI Miftahul Ula Nganjuk, 2021)
This study aims to determine whether or not there is an influence of self-concept on learning outcomes of civics education, the influence of self-concept on emotional intelligence of class X State Senior High School in Pasar Rebo District. The population of this research is all students of class X State Senior High School in Pasar Rebo District. The schools that were sampled were SMAN 39, SMAN 98, and SMAN 106. The total population of the three schools was 574, using Isaac and Michael's tables, obtained a sample of 221 students. The results of this study prove that self-concept has a significant influence on student citizenship education learning outcomes with a correlation level of r132 of 0.361 or 3.6%.